Paving the way for coastal resources management the Bolinao experience (1993-97). - McManus, L. T.; Menez, M. A. J.; Alino, E. M.; Ferrer, E. M.; Dizon, J. C. A. (eds.). (U.P. MSI, UP CSWCD and Haribon Foundation for the conservation of natural resources, Inc., International Development Research-Canada, CBCRM, 2001)
A terminal report of the Project Community-Based Coastal Resources Management (CBCRM) Centre File: 94-0021/40156
Keywords: Coastal zone management